Nutricosméticos no processo de envelhecimento de mulheres - Battisti, Betina Zimmermann (2001)
The aging process of the skin, hair and nails is triggered from a combination of internal and external factors, presenting characterizations show that the cellular and molecular alterations, which progressively reduce the ability of homeostasis. We sought to determine whether the ingestion of capsules containing substances organic silicon and cyanobacteria can mitigate the aging process of the skin, nails and hair. The study was characterized as blind randomized trial with a control group and a sample of 45 women, aged between 40 and 60 years, divided into three groups of 15 women: control group (CG), organic silicon group (SO) and group Spirulina platensis (SP). To characterize the sample was applied at time zero (pre-treatment) Facial Protocol Assessment (PAF). At time zero was also applied to a visual analogue scale (VAS) of four points which measures the degree of fragility of nails and a measurement of body weight. In the time period (post-treatment) the instruments for data collection were again measured body weight and application of VAS, and Scale Global Aesthetic Improvement (GAIS) and Questionnaire Subjective Interpretation of the quality of hair, taking into consideration the criteria combing, softness, shine, growth and decline. In this context, the application of PAF showed homogeneity in age between the groups, 82.2% of participants make use of cosmetics, 75.6% use sunscreen; 51.1% have had some type of treatment for skin , 17.8% have a family history of cancer, 13.3% were smokers, 44.4% are physically active, 33% are in menopause, 100% of the sample have wrinkles, 53.3% and 33% mixed skin present photoaging. In the evaluation of the skin and nails, both treatments showed significant results (p<0.05), but in compareção between groups, the SP group showed better results. In assessing the quality of the hair, the criteria analyzed combing, softness, shine and growth showed positive results in both groups, but the SO group showed better results. Referring to body weight, there was no significant difference, but we can consider that the group showed less weight gain after treatment was in the SP group. It was concluded that there was an increase in the improvement of the hair, nails and skin, proving the efficiency of the treatment of nutri cyanobacteria and organic silicon